2009
DOI: 10.1111/j.1365-2044.2008.05738.x
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of systolic arterial pressure alarms using statistics‐based versus threshold alarms*

Abstract: SummaryThreshold systolic arterial pressure alarms often use pre-operative values as a guide for intra-operative values. Recently, two systems (normalisation and principal component analysis) have been described that use the 'current' systolic arterial pressure and the change in systolic arterial pressure over a preceding time interval to generate an alarm based on units of standard deviation. Normalisation and principal component analysis techniques should prioritise alarms for clinically significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similar severity ranking showed success in increasing alert acceptance rate by 50%, despite a 60% increase in alert events [35]. Other studies attempting to reduce noise, however, achieved limited or mixed results [36][37][38][39][40][41][42][43][44][45].…”
Section: Background and Significancementioning
confidence: 70%
See 1 more Smart Citation
“…Similar severity ranking showed success in increasing alert acceptance rate by 50%, despite a 60% increase in alert events [35]. Other studies attempting to reduce noise, however, achieved limited or mixed results [36][37][38][39][40][41][42][43][44][45].…”
Section: Background and Significancementioning
confidence: 70%
“…The best models showed that by allowing 30 seconds of delay, false alarms can be better distinguished from true alarms; the best models were able to achieve 80% reduction in false alarms, missing 1% of true alarms. Studies focusing on pulse oximetry to reduce peripheral capillary oxygen saturation (SpO 2 ) false alarms, intracranial pressure alarms, and general vital sign monitoring alarms found mixed results ranging from 25% to 47% in alarm reduction, with 0% to 5% false-negative rates [42][43][44][45]. A more recent study showed that, by increasing delayed time within 3 min for alarms with physiologic monitoring waveforms, as well as including electrocardiography, SpO 2 , and arterial blood pressure, an ML model can achieve slightly better performance but fails to stably generalize to unseen data [52].…”
Section: Principal Findingsmentioning
confidence: 99%